Student Perception of Online Learning Media Platform During the Covid-19 Pandemic - Fahruddin, Fahruddin; Jana, Padrul; Setiawan, Johan; Rochmat, Saefur; Aman, Aman; Yuliantri, Rhoma Dwi Aria (Universitas Pendidikan Ganesha, 2022)
Learning during the Covid-19 Pandemic requires lecturers to be able to adapt by using online learning platforms. As a result, there are different perceptions of students regarding the effectiveness of each of these platforms. The study aimed to analyze differences in students' perceptions about the effectiveness of using WhatsApp, Google Classroom, and Zoom platforms. This research method uses quantitative methods to measure the level of perception and is combined with qualitative methods to analyze student perception. The data collection method is done by distributing questionnaires through Google forms to students. The analysis used is a quantitative analysis using statistical calculation and qualitative analysis to analyze student perception. The results showed that the difference in perception in WhatsApp and Google Classroom usage was significant with an average difference of 16.933 which means WhatsApp’s perception levels are higher than Google Classroom. The difference in perception in WhatsApp and Zoom usage is significant with an average difference of 15.2 which means WhatsApp's perception level is higher than zoom. The difference in perception in Zoom and Google Classroom usage is insignificant with an average difference of 1.733 which means Zoom’s perception rate is slightly higher than Google Classroom. The study concluded that student perceptions were higher on the WhatsApp Group platform, then zoom, and finally Google Classroom. Online learning should first use the WhatsApp platform, then zoom, and finally Google Classroom.